Prevalence of celiac disease in a large cohort of young patients with type 1 diabetes. Issue 4 (3rd April 2019) - Puñales, Marcia; Bastos, Marilia Dornelles; Ramos, Ana Regina L.; Pinto, Raquel Borges; Ott, Eduardo A.; Provenzi, Valentina; Geremia, César; Soledade, Maria Antônia; Schonardie, Ana Paula; da Silveira, Themis R.; Tschiedel, Balduino
Abstract : Background: Serological screening for celiac disease (CD) allows the identification of individuals genetically predisposed, as type 1 diabetes mellitus (T1DM). However, the diagnosis is confirmed by intestinal biopsy. The aim was to determine the prevalence of immunoglobulin‐A anti‐tissue transglutaminase antibodies (IgA‐tTG) and CD in a large cohort of young T1DM patients. Methods: Screening for CD was randomly conducted in 881 T1DM by IgA‐tTG and total IgA. Individuals with positive antibodies were referred to endoscopy/duodenal biopsy. Results: The age of the cohort at the screening was 14.3 ± 5.9 years and at T1DM onset was 7.9 ± 4.4 years. The prevalence of positive serology was 7.7%. Median IgA‐tTG levels were 117.7 U/mL (interquartile range [IQR] 35.7‐131.5 U/mL). Of the 62 duodenal biopsy, CD was diagnosed in 79.0%, yielding an overall prevalence of 5.6%. The mean age of CD patients was 15.6 ± 6.5 years and, at T1DM onset was 6.3 years (4.0‐9.9 years). The modified Marsh ‐Oberhuber histological classification was 22.5% (3a), 36.7% (3b), and 40.8% (3c). In the biopsy‐proven patients, T1DM onset occurred at slightly younger ages (6.3 vs 9.7 years, P = 0.1947), gastrointestinal (GI) manifestations, predominantly abdominal pain and distension, were more prevalent (71.4% vs 38.5%, P = 0.027) and higher IgA‐tTG titers (128.0 vs 26.3 U/mL, P = 0.0003) were found than in those with negative‐biopsies. Conclusion: Our results demonstrate the prevalence of 7.7% of IgA‐tTG and 5.6% of CD in T1DM patients in South Brazil and, emphasize the importance of the screening in high‐risk individuals. Furthermore, the presence of GI manifestations and higher IgA‐tTG titers strongly suggest the diagnosis of CD.